Guidelines for Laboratory Design : Health and Safely Consideration - Louis J DiBerardinis (Wiley, 2011)
The construction of new laboratory buildings or the renovation of existing ones requires close communication between laboratory users, project engineers, architects, construction engineers, and health and safety personnel. All too often, health and safety considerations are overlooked or slighted and are not sufficiently incorporated into designs. Guidelines for Laboratory Design: Health and Safety Considerations, Third Edition provides reliable design information related to specific health and safety issues that need to be considered when building or renovating laboratories. With an increase in the number of laboratory renovations due to lower costs and faster end results compared to constructing new buildings, the latest edition of Guidelines for Laboratory Design, which includes new chapters on laboratory renovation, is particularly timely. This well-established and respected volume also includes a vital section on design guidelines for commonly used laboratories and features separate chapters on a wide array of laboratory types. In addition, the updated material contains: -A new section on design for environmental preservation through the operation and maintenance of health and safety -The latest information on laboratory ventilation and safety systems -Incorporation of "green" laboratory design techniques -Discussions on the architectural, engineering, regulatory, and health and safety aspects unique to the renovation process A wide range of professionals-including those in industrial hygiene, chemical health and safety, laboratory management, and architectural and engineering firms handling laboratory construction and renovation-will find the latest edition of Guidelines for Laboratory Design: Health and Safety Considerations essential reading.